Advances in Boar Semen Cryopreservation - Heriberto Rodriguez-Martinez; Margareta Wallgren (Veterinary Medicine International)
The present paper highlights aspects of the cryopreservation of boar semen, a species with particular large, fractionated ejaculates, and a cumbersome cryotechnology that had prevented its commercial application. With the dramatic increase of use of liquid pig semen for artificial breeding over the past decade, developments on cryopreservation alongside the routine use of stud boar semen for AI had been promoted. Recent advances in our laboratory, accommodating the best use of portions of the sperm-rich fraction of the ejaculate for cryopreservation of the sperm-peak portion (P1) and parallel use of the rest of the collected ejaculated spermatozoa, appears as a suitable commercial alternative.